The Interdependence of Types of Musical Activities in Music Culture Classes - Qobiljon Toshtemirov Qubbijonovich (International Journal on Orange Technologies, 2021)
Today, music plays an important role in the formation of a person, actively influencing his emotions and psyche. One of the main tasks of secondary schools is to bring students into the world of sophistication and spiritual education. In doing so, the teacher introduces the children to a particular piece of music and performs it in an expressive, "live" way, drawing the students' attention to the work. Improving their speech, thinking skills, and outlook will also have an active effect on their emotions. In the article, the author provides information on the organic relationship of types of musical activities in music culture classes.